Cytotoxic T-Cells in HIV-1: "The Good" and "The Bad" - Glanville, JM (2012)
CD8+ T-cell antigen sensitivity is critical for optimal control of persistent viral infections, including HIV-1. The devastating HIV-1 pandemic may be countered by development of a cytotoxic T lymphocyte based vaccine if qualities associated with protection can be defined at the molecular level. However, the heterogeneity of the total viral-specific CTL response confounds identification of protective correlates and T-cell sensitivity is no exception and remains controversial. To address this issue we reduced the heterogeneity of the HIV-1 CTL response to single units, generating 19 CTL clones that recognise the same HIV-1 derived epitope restricted by HLA B*08. Correlation of functional assays directly with the ability of each clone to control HIV-1 replication in vitro, the “viral suppression assay,” identified antigen sensitivity as a key quality for anti-viral efficacy. Remarkably, four clones from this panel, isolated from one individual, a long-term non-progressor, all used an identical TCR yet had distinct antigen sensitivity and suppressive activity. Two of these clones were characterised in detail, and had distinct cytokine profiles, regulated by epigenetic mechanisms, and differential expression of a group of cell surface receptors with the potential to modulate the signalling threshold to antigen. Expression of the TNFα locus of the high sensitivity clone with “Good” suppression was repressed by DNA methylation. Understanding how CTL qualities required for optimal control of HIV-1 replication differentiate and are then enriched in the total CTL response, and if repression of TNFα contributes to this process, will contribute to rational vaccine design. This is the first evidence that avidity maturation in CD8+ T cells with the same TCR affinity occurs in viral infections in humans as reported in the mouse. This suggests the induction of high sensitivity CTL will be critical for an effective HIV-1 vaccine, but offers hope that this can be achieved even in individuals without protective HLA alleles, by further exploration of peripheral avidity maturation and epigenetic regulation of the HIV-1 specific CD8+ T-cell response.